2017
DOI: 10.1177/0305735617690245
|View full text |Cite
|
Sign up to set email alerts
|

Self-regulation of teenaged pianists during at-home practice

Abstract: Professional musicians employ self-regulation and deliberate practice strategies when learning music. Although self-regulation is difficult for beginners, presumably students practice deliberately as music becomes more difficult and they develop musical skills. It is not clear to what extent intermediate piano students self-regulate during learning. This study explored practice strategies used during at-home practice of nine intermediate-level teenaged piano students. Over a two-month period, piano students re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 30 publications
5
33
0
Order By: Relevance
“…Secondly, participants in these studies reported that they tended to concentrate on reading from notation, “technicalities” and playing through pieces during practice, overlooking matters of interpretation because of the challenges of instrumental playing. This is in line with research that found that young musicians tend to have inefficient practice strategies and are inclined to play through pieces (e.g., Pitts and Davidson, 2000 ; Pitts et al, 2000 ; McPherson and Renwick, 2001 , 2010 ; Austin and Berg, 2006 ; Lisboa, 2008 ; Hallam et al, 2012 ; Pike, 2017 ). Thirdly, questionnaire answers suggested that the challenges of instrumental music learning were balanced by the rewards of music participation.…”
Section: Introductionsupporting
confidence: 89%
See 3 more Smart Citations
“…Secondly, participants in these studies reported that they tended to concentrate on reading from notation, “technicalities” and playing through pieces during practice, overlooking matters of interpretation because of the challenges of instrumental playing. This is in line with research that found that young musicians tend to have inefficient practice strategies and are inclined to play through pieces (e.g., Pitts and Davidson, 2000 ; Pitts et al, 2000 ; McPherson and Renwick, 2001 , 2010 ; Austin and Berg, 2006 ; Lisboa, 2008 ; Hallam et al, 2012 ; Pike, 2017 ). Thirdly, questionnaire answers suggested that the challenges of instrumental music learning were balanced by the rewards of music participation.…”
Section: Introductionsupporting
confidence: 89%
“…Secondly, it is important to understand why children tend to focus on technique and note reading during practice rather than on expression and communication (see Pitts and Davidson, 2000 ; Pitts et al, 2000 ; McPherson and Renwick, 2001 ; Austin and Berg, 2006 ; Lisboa, 2008 ; McPherson and Renwick, 2010 ; Pike, 2017 ), and why there seems to be a focus on these elements of instrumental playing in lessons too (see Rostvall and West, 2003 , 2005 ; West and Rostvall, 2003 ; Karlsson and Juslin, 2008 ). The questionnaire findings reported above ( Meissner, 2018 ) support the view that this focus on technique and notation in instrumental practice and lessons is generated by the difficulties which children experience when they start learning their instruments.…”
Section: Theoretical Framework and “Toolkit” For Teaching Young Musicmentioning
confidence: 99%
See 2 more Smart Citations
“…Questions regarding practice might assist pupils to start reflecting on this, which could be a useful step to developing self-regulated practice habits (cf. McPherson and Renwick, 2001;Hallam et al, 2012;Pike, 2017).…”
Section: Discussionmentioning
confidence: 99%